2015
DOI: 10.1017/neu.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

Dietary magnesium deficiency affects gut microbiota and anxiety-like behaviour in C57BL/6N mice

Abstract: Magnesium deficiency altered behavior. The duration of magnesium deficiency is suggested to influence behaviour in the evaluated test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Several previous studies have shown that calcium supplementation results in increased gut microbial diversity in mice [ 46 , 47 ]. Moreover, magnesium-deficient diets have been shown to adversely affect gut microbial composition, and to promote both anxiety- and depressive-like behaviour in mice [ 48 , 49 ]. However, there is little evidence to date on the effects of magnesium supplementation on gut microbial diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that calcium supplementation results in increased gut microbial diversity in mice [ 46 , 47 ]. Moreover, magnesium-deficient diets have been shown to adversely affect gut microbial composition, and to promote both anxiety- and depressive-like behaviour in mice [ 48 , 49 ]. However, there is little evidence to date on the effects of magnesium supplementation on gut microbial diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The anxiolytic potential of Mg has been demonstrated in rodent models. Naturally and experimentally induced hypomagnesemia elevates anxiety states in mouse models [12,21,42,43]. Blood plasma and brain Mg levels are also significantly correlated with anxiety-related behavioral responses in rodents [44].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a significant correlation was found between the gut microbiota of the diet deficient in Mg and a decrease in hippocampal IL-6 levels, suggesting that this immunemodulation could be the mechanism by which diet induced changes in the gut microbiota composition alter behaviour [61]. A similar study found that a diet deficient in Mg decreased bacterial diversity and altered anxiety-like behaviour [62].…”
Section: Dietary Interventionsmentioning
confidence: 84%